A Scale to Measure the Joy in Work of Doctors: Development, Validity, and Reliability - Zhang, Zemiao; Hu, Yinhuan; Chen, Hao; Zhu, Weilin; Li, Dehe; Zhu, Ximin; Wu, Xiaoyue; Li, Jiayi (Frontiers in Public Health, 2021)
Background: The aim of this study is to develop a scale and evaluate its’ validity and reliability to measure the joy in work of doctors. Methods: Based on literature review and panel discussion, the scale framework and item pool were determined. Next, the items were modified by two rounds of expert consultation. Then the pre-investigation was applied and the formal version of scale was formed. Last, the reliability and validity of the scale were tested with 426 physicians. Results: The scale was composed of four dimensions: work autonomy needs, competency identification needs, competency perception needs and work relationship needs. Each dimension had 7 items, and both reliability and validity were acceptable. The Cronbach α coefficient and half-reliability coefficient of the whole scale were 0.954 (＞0.9) and 0.974 (＞0.9). The Spearman correlations of item-total score ranged from 0.556 to 0.749, indicating a good-item total score correlation. The χ 2/ df, RMSEA, RMR, GFI, CFI, and TLI, CFA of the maximum likelihood method supported a good fit with the model. Conclusions: Based on the self-determination theory, this study was the first to construct a scale of doctors' work happiness. It has good validation and reliability, which is useful for doctors and medical institutions to take steps to improve happiness.